A case of endogenous mycotic endophthalmities that developed in a patient following dental surgery undergoing long-term steroid therapy - Hamamoto, Yoshioki; Kobayashi, Takehito; Sakurai, Hiromasa (Journal of Japanese Society of Dentistry for Medically Compromised Patient, 2007)
We herein present a case that developed endogenous mycotic endophthalmities following ambulatory dental surgery in our department's outpatient clinic. The patient is a 25 years old female patient who sought dental treatment trimus resulting from stomatognathic dystonia. Her medical history revealed concurrent multiple sclerosis and long-term steroid therapy of approximately 8 years. The patient was hospitalized and our objective for treatment was the correction of trimus. Postoperatively, the patient's nutritional management was conducted through the IVH but the patient developed catheter sepsis followed by the development of pulmonary mycosis. The patient was then referred to the Department of Internal Medicine for evaluation and consultation. The patient also developed endogenous mycotic endophthalmitis on the ninth day after commencement of MCFG treatment. Upon recommendations by the ophthalmologist the antifungal agent was changed from MCFG to VRCZ. After the change in antifungal agent, pulmonary mycosis and the endogenous mycotic endophthalmitis improved and subsided. Furthermore, for patients diagnosed with carcinoma, under treatment with immunosuppressive drugs and intravenous hyperalimentation, the time of onset and immediate medical evaluation and response are extremely important issues for management and determining the course of treatment for these patients and one must consider the possibility of the presence of a deep-seated mycotic infection.